Absolute content of bone component in the body of Kyrgyz children with different somatotypes in the early childhood - K. Zhanybek kyzy; K. Sakibaev; A. Sattarov; G. Dzholdosheva; E. Zholdosheva (Zaslavsky O.Yu., 2023)
Background. Improving pediatric observation globally and in Kyrgyzstan is essential for early detection of developmental issues and monitoring normal physical parameters. The purpose of the study was to investigate the indicators of bone composition in children of Kyrgyz nationality of both sexes in the early childhood period. Materials and methods. To achieve the goal, 800 children from 4 to 7 years old were examined using anatomical-anthropometric and bioimpedance methods. Results. It was revealed that the absolute content of bone component in male respondents at the age of 4 years ranges from 3.24 to 5.17 (4.10 ± 0.01) kg, 5 years - from 3.27 to 5.81 (4.26 ± 0.01) kg, 6 years - from 3.34 to 5.87 (4.39 ± 0.01) kg and 7 years - from 3.23 up to 6.02 (4.59 ± 0.01) kg. The absolute index of the bone component in 4-year-old girls has an individual variability of 3.04-5.17 (3.97 ± 0.01) kg, 5-year-old - 3.27-5.61 (4.20 ± 0.01) kg, 6-year-old - 3.34-5.77 (4.34 ± 0.01) kg and 7-year-old - 3.43-6.02 (4.40 ± 0.01) kg. Conclusions. The highest bone content was found in individuals with muscular somatotype, while the lowest values were in asthenoid and thoracic somatotypes for both males and females. Boys had higher bone component index at ages of 4 and 7.